2015
DOI: 10.1007/s11666-015-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Microscopic Study of Suspension Plasma-Sprayed Zirconia Coatings with Different Microstructures

Abstract: The present paper is focused on the characterization of the differences between two microstructures that can be obtained using SPS technology, namely (i) columnar and (ii) two-zone microstructure including lamellas and fine unmelted particulates. The optimization of spray parameters was made, and the advanced microstructural studies of obtained coatings were performed. The work was focused on zirconia stabilized by yttria (YSZ, ZrO 2 + 14 wt.% Y 2 O 3 ) and both by yttria and ceria (YCSZ, ZrO 2 + 24 wt.% CeO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…10, especially at troughs of the undulated substrate surface with a higher drag force generated by a higher gas flow. Results in this study as well as previous studies 18,19,26,32,33,43 confirm that both columnar and DVC YSZ coatings developed in SPS are results from the successive deposition of much finer splats. 10.…”
Section: (5) Mechanism For Columnar and Dvc Sps Coatings Formationsupporting
confidence: 89%
See 2 more Smart Citations
“…10, especially at troughs of the undulated substrate surface with a higher drag force generated by a higher gas flow. Results in this study as well as previous studies 18,19,26,32,33,43 confirm that both columnar and DVC YSZ coatings developed in SPS are results from the successive deposition of much finer splats. 10.…”
Section: (5) Mechanism For Columnar and Dvc Sps Coatings Formationsupporting
confidence: 89%
“…It is confirmed that the undulated substrate surface originated from the hemispherical surface of alloy particles which were not fully melted during HVOF processing. As reported, 19,32,33,39 the finer the in-flight ceramic droplets are, the easier for them to follow the plasma gas flow with increased lateral velocity along the substrate surface. Figure 9(c) displays a similar case in C2 with 6.5 mm torch nozzle.…”
Section: (5) Mechanism For Columnar and Dvc Sps Coatings Formationmentioning
confidence: 87%
See 1 more Smart Citation
“…The views were created automatically by assembling four SEM micrographs, taken by symmetrically located BSD detectors (Phenom G2 pro, Phenom-World B.V., Eindhoven, the Netherlands). More details on SFS are provided in work [25].…”
Section: Characterization Of Coatings Topographymentioning
confidence: 99%
“…The particles of the liquid suspension used in SPS can be of submicron size, i.e., \1 lm (Ref 1), whereas 10-100 times larger particle are used in APS ( Ref 2). The smaller particles are more influenced by the plasma jet flow as it interacts with the substrate (Ref 3) and the difference in droplet flight path leads to formation of a columnar structure (Ref 4,5). Hence, the coating build-up occurs in a different manner as compared to conventional APS spraying.…”
Section: Introductionmentioning
confidence: 99%